Stable Sulfur‐Intercalated 1T′ MoS2 on Graphitic Nanoribbons as Hydrogen Evolution Electrocatalyst. (1st October 2018) - Ekspong, Joakim; Sandström, Robin; Rajukumar, Lakshmy Pulickal; Terrones, Mauricio; Wågberg, Thomas; Gracia‐Espino, Eduardo
Abstract: The metastable 1T′ polymorph of molybdenum disulfide (MoS2 ) has shown excellent catalytic activity toward the hydrogen evolution reaction (HER) in water‐splitting applications. Its basal plane exhibits high catalytic activity comparable to the edges in 2H MoS2 and noble metal platinum. However, the production and application of this polymorph are limited by its lower energetic stability compared to the semiconducting 2H MoS2 phase. Here, the production of stable intercalated 1T′ MoS2 nanosheets attached on graphitic nanoribbons is reported. The intercalated 1T′ MoS2 exhibits a stoichiometric S:Mo ratio of 2.3 (±0.1):1 with an expanded interlayer distance of 10 Å caused by a sulfur‐rich intercalation agent and is stable at room temperature for several months even after drying. The composition, structure, and catalytic activity toward HER are investigated both experimentally and theoretically. It is concluded that the 1T′ MoS2 phase is stabilized by the intercalated agents, which further improves the basal planes′ catalytic activity toward HER. Abstract : The metastable 1T′ polymorph of MoS2 is an excellent catalyst toward the hydrogen evolution reaction. However, its production is limited by its lower energetic stability compared to the semiconductor 2H MoS2 phase. Stabilization of the 1T′ polymorph can be achieved through intercalation of sulfur‐based compounds without adversely affecting its catalytic properties.